2013
DOI: 10.4328/jcam.1151
|View full text |Cite
|
Sign up to set email alerts
|

Age and Dialysis Adequacy in Maintenance Hemodialysis Patients

Abstract: ÖzetAmaç: Dializin optimal dozu ve sıklığı sorunu, dializ tedavisi alımında en önemli sorun başlığı olmuştur. Biz yaşın, bazı hemodiyaliz parametrelerin, özellikle üre reduksiyon hızı ile (URR) hemodializ yeterliliği üzerindeki etkisini değerlendirmeyi ve bu parametreleri diabetli ve diabetli olmayan hastalar arasında karşılaştırmaya çalıştık. Gereç ve Yöntem: İdame hemodiyaliz tedavisi alan End-stage (SON EVRE) hastalar dikkate alındı. Üre redüksiyon hızı ve boy kilo endeksleri hesaplandı. Bulgular: Tümü 60 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(53 reference statements)
1
0
0
Order By: Relevance
“…In the index study, we have found that the elderly population had more than two times higher risk of having inadequate HD. These findings complement previous reports from Iran [19] and Rwanda [10] where there was a significant negative correlation between age and inadequate HD. Also, in Tanzania the same findings were previously reported where the older population of 40 years or older comprised the majority of patients with inadequate HD [12].…”
Section: Discussionsupporting
confidence: 91%
“…In the index study, we have found that the elderly population had more than two times higher risk of having inadequate HD. These findings complement previous reports from Iran [19] and Rwanda [10] where there was a significant negative correlation between age and inadequate HD. Also, in Tanzania the same findings were previously reported where the older population of 40 years or older comprised the majority of patients with inadequate HD [12].…”
Section: Discussionsupporting
confidence: 91%